Effects of water stress and nutrient management on the performance of tomato - Rasul Miah, Md. Golam; Karim, A. J. M. Sirajul; Islam, Md. Moshiul; Islam, Md. Dhin; Kamal, Mohammed Zia Uddin (International Journal of Environment, Agriculture and Biotechnology, 2023)
Management of nutrient and water scarcity are very important for getting higher yield of tomato specially in winter season in Bangladesh. The application of different fertilizer and manures increase the availability of nutrients which to stimulate plant growth that lead to enhance stress tolerance. Therefore, the main aim of this study is to investigate how different nutrients management practices improves growth by reducing impacts of water stress. Tomato plants were grown in field condition and different growth parameters such as height, root dry weight and shoot dry weight were measured. Yield and yield attributes of tomato were also determined. Recommended fertilizers along with organic manures application improve the growth and yield of tomato plants. On the other hand, growth and yield of tomato was lowest for no fertilization and manures treatment. This study improves our understanding about how nutrient management in water stress increase the growth and yield of tomato plant.